The Influence of Halal Awareness, Digital Marketing and Influencers on Purchasing Decisios About Halal Cosmetics - Zubaidah Nikiulu, Adinda Fauzah; Nurmasari, Nuraini Desty (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Purpose – This study aims to examine the effects of halal awareness, digital marketing, and influencer marketing on purchase decisions among Generation Z consumers in Malang City.     Design/methodology/approach – This study employs a quantitative explanatory research design to analyze the relationships among halal awareness, digital marketing, influencer marketing, and purchase decisions. The respondents consisted of 300 Muslim Generation Z consumers in Malang City who had purchased halal cosmetic products through e-commerce or used halal cosmetic brands promoted by influencers or brand ambassadors. Data were collected through structured questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics version 26.   Findings – The results indicate that halal awareness, digital marketing, and influencer marketing each have a positive and significant effect on purchase decisions. These findings suggest that religious awareness combined with digital promotional strategies and influencer endorsements plays an important role in shaping purchasing behavior among Generation Z consumers.   Originality/value – This study contributes to halal marketing and digital consumer behavior literature by integrating halal awareness, digital marketing, and influencer marketing as determinants of purchase decisions in the halal cosmetics industry. The findings provide practical implications for cosmetic companies targeting Generation Z consumers in Muslim-majority markets.